(untitled) (Web of Teachers: Inderscience Research, 2024)
This article investigates one of the main issues of modern linguistics such as the semantics of the verb, its cognitive modeling and the lexical-semantic system. However, without a complete study of the semantic aspects of a linguistic phenomenon, it is impossible to reveal fully its essence and nature. Verbs are known to be rich in grammatical forms and categories compared to other parts of speech. At the same time, verbs are paradigmatically more diverse and syntagmatically comprehensive. The peculiarity of verbs is that they occupy the most important place in the vocabulary of the language and the central place in the sentence. That is why in works on ancient linguistics the verb is allocated to a separate category. The versatility of the verb is manifested in its semantic properties and classification.